The elements of teaching - Banner, James M., 1935- 4 0 16; 1930- Cannon, Harold C.; 5 (New Haven : Yale University Press, 1997)
The authors describe the specific intellectual, moral, and emotional qualities they believe a person must possess in order to be a successful teacher, and use portraits of fictional teachers to illustrate how those characteristics promote learning and understanding.
Professional.
Keywords: 2 -- 0; 6; Teaching.;Teacher effectiveness.;Teachers.; 20; 2